Cereal grain-based functional beverages: from cereal grain bioactive phytochemicals to beverage processing technologies, health benefits and product features. Issue 9 (30th March 2022) - Xiong, Yun; Zhang, Pangzhen; Warner, Robyn Dorothy; Shen, Shuibao; Fang, Zhongxiang
Abstract: Increased consumer awareness of health and wellness has promoted a high demand for foods and beverages with functional and therapeutic properties. Cereals, apart from being important staple crops and primary sources of energy and nutrition, are replete with bioactive phytochemicals with health properties. Cereal grains contain a diverse range of bioactive phytochemicals including phenolic compounds, dietary fibers, carotenoids, tocols, phytosterols, γ -oryzanol, and phytic acid and therefore have great potential for processing into functional beverages. Although there are a variety of cereal grain-based beverages produced world-wide, very little scientific and technological attention has been paid to them. In this review, we have discussed cereal grain-based functional beverages based on 3 main categories: cereal grain-based milk alternatives, roasted cereal grain teas, fermented nonalcoholic cereal grain beverages. The processing techniques, health properties and product features of these beverages are elaborated, and the challenges and future perspectives are proposed. As the food market becomes increasingly diverse, cereal grain-based beverages could be a promising new category of health functional beverages in our daily life.